Monocyte to High‐Density Lipoprotein Ratio Is Associated With Carotid Plaque: A Retrospective Cohort Study - Shuang Liu; Xinlei Miao; Manling Hu; Ziping Song; Xiaoling Xie; Yuting Sun; Meng Li; Guimin Tang; Song Leng (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The level of monocyte to high‐density lipoprotein ratio (MHR) is associated with cardiovascular diseases. Carotid plaque (CP) is an independent risk factor for cardiovascular diseases. However, evidence for association of MHR with risk of CP is scarce. Methods and Results This study involved 5260 participants aged >18 years old from the Dalian health management cohort in 2014 to 2022. The subjects were stratified into 4 groups based on the quartile of the MHR at baseline. Multivariable‐adjusted Cox regression models were used to calculate the MHR‐associated risk of incident CP. The mean age of the population was 46.14 years and 58.8% (n=3093) of the participants were male. Seven hundred fifty‐nine (14.4%) of participants developed new‐onset CP. During the follow‐up of 9725 person‐years, the MHR at quartile 4 group experienced a significantly higher incidence of CP than the MHR at quartile 1 group (56.9 versus 101.5 per 1000 person‐years; log‐rank P <0.001). Compared with the MHR at quartile 1 group, the MHR at quartile 4 group had the highest CP risk (hazard ratio. 1.389 [95% CI, 1.059–1.823]) and 10‐year cardiovascular risk (China‐PAR Project score: odds ratio, 1.975 [95% CI, 1441–2.708 in men]; odds ratio, 6.015 [95% CI, 1.949–18.564 in women) (P <0.001). Meanwhile, similar results were observed in multiple sensitivity analyses. Conclusions Elevated MHR was associated with the risk of CP. The assessment and management of MHR is helpful for the early detection of patients with CP and the primary prevention of cardiovascular diseases.